The Relationship Between Instagram Photo Activity and Body Dissatisfaction in Emerging Adult Women Mediated by Sociocultural Attitudes - Linawati, Bernadea; Helmi, Avin Fadilla (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Body dissatisfaction is a problem experienced by emerging adult women from various cultures, including those from Asia. The ease of accessing photo-based platforms like Instagram, and sociocultural attitudes may worsen the body image of social media users. Instagram posts can reflect ideal standards that are difficult to attain and the internal or external pressure on women to meet them. This study aimed to measure the role of sociocultural attitudes, i.e., internalization of beauty standards and social pressure, as a mediator of the relationship between Instagram photo activity and body dissatisfaction of women in emerging adulthood. This research involved 311 (M age=21.6, SD=1.87) female Instagram users, aged 18 to 24. This quantitative research used survey as the data collection method and regression with a mediation model for data analysis. Results showed that sociocultural attitudes have a positive role in the relationship between Instagram photo activity and the body dissatisfaction of adult female Instagram users. Future research can incorporate different participant groups and explore alternative models to measure the variables in this study.